Vliv intenzity odlistění na kvalitu hroznů - Zugárková, Petra (Mendelova univerzita v Brně, Zemědělská 1/1665, 613 00 Brno, http://mendelu.cz/, 2014)
The aim of this thesis was to establish experiment with different dates of defoliation in the zone of grapes, evaluate the infestation by Botrytis cinerea putrefaction, monitor the development of qualitative and quantitave parametres and the content of phenolic compounds. The experiment was conducted at white wine grapes variety Ryzlink rýnský a blue wine grapes variety Carmenere. The literary section describes leaf and its area, microclimate of leaf walls, qualitative parametres, balance of the vineyard, green works, Botrytis cinerea and partial defoliation. Within the experiment were evaluated and controled at the defoliated variation: quality parameters (sugar content, titratable acid pH, assimilable nitrogen, amount of glucose and fructose, tartaric acid and malic acid), infestation by Botrytis cinerea putrefaction, content of phenolic compounds. Measurements were performed at the Department of viticulture and viniculture in faculty of Horticulture in Lednice. Used instruments: TitroLine - pH, titratable acid, assimilable nitrogen; HPLC - tartaric acid, malic acid, glucose and fructose; Spectrophotometer - the content of phenolic compounds; Digital Scale - weight of the grapes. As the most appropriate option in terms of measured parameters was selected the option before the flowering and during the flowering of Ryzlink rýnský and Carmenere.
Keywords: Ryzlink rýnský; odlistění; list; Carmenere; kvalitativní parametry